About experimental discovery of type II superconductivity - Shepelev, A. (Вопросы атомной науки и техники, 2022)
The date and authorship of the experimental discovery of the phenomenon of type II superconductivity is specified. “It is a fascinating testament to Shubnikov's great originality and to the terrible times that deprived him of his life and we all of the fruits of the science for so long. Even now, many do not really understand the breakthrough made in Kharkov”.
From the letter of 31 December, 2008, written by Shubnikov Professor D. Larbalistier, Director of Applied Superconductivity Center, USA, on reprinting in English the article. Уточнюється дата і авторство експериментального відкриття явища надпровідності II роду. Уточняется дата и авторство экспериментального открытия явления сверхпроводимости II рода.